Responding to Complexity: Microfinance MIS Service Providers as Complex Adaptive Systems. Issue 2 (July 2015) - Sinha, Gaurav
Abstract: The general systems theory is widely used to study organisations. It offers concepts and metaphors to study how organisations function. In tune with the contemporary approaches in systems thinking, this article examines responses of small management information system (MIS) service providers in the microfinance sector. These small service providers play a pivotal role in defining the growth strategy of the sector, in general, and many microfinance institutions, in particular. Precisely, the study seeks answers to the following questions: What approaches do the small (or associated) service providers in the microfinance sector follow to run their organisations? Given the present complex environment, where do such approaches lead them to or what are the issues they face? How do these service providers respond to these challenges? This article is an attempt to map responses of MIS services providers in dealing with complexities and the ecosystem in which they operate. It proposes an evolving framework based on some key elements drawn from systems theory. Given the huge number of micro and small enterprises across the world, the present study expects to provide insights into how small entrepreneurial organisations operate, the challenges they face and the steps they adopt to address these challenges.